2015
DOI: 10.1016/j.ijrobp.2015.07.331
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Risk Meningioma: Initial Outcomes from NRG Oncology/RTOG-0539

Abstract: (Q1, 0.25; Q3, 0.44) for metastatic lesions, P < .0001. Significant differences were noted based on the site of breast metastases. The median RSIs for metastases in descending order of radioresistance were bone (0.50), brain (0.44), skin (0.44), ovary (0.43), liver (0.34), lung (0.32), and lymph nodes (0.31), P < .0001. When we restricted our analysis to patients with both a primary and metastatic lesion available for analysis (n Z 99), similar differences in radiosensitivity were noted. Primary lesions contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 0 publications
5
60
0
1
Order By: Relevance
“…The preliminary results (in abstract form) of the phase 2 NRG/Radiation Therapy Oncology Group (RTOG) 0539 study found that a combination of surgery/RT led to significantly improved progression-free survival in a group of patients treated for recurrent grade 1 lesions and completely resected atypical lesions. 26 This will be tested in the future with NRG Oncology protocol BN-003 and the ongoing Radiation versus Observation following surgical resection of Atypical Meningioma (ROAM)/European Organization for Research and Treatment of Cancer (EORTC)-1308 trial, for which, based on the results of the current study, we would support patient enrollment for the evaluation of disease-free-survival. 27 Although studies to date have demonstrated improvement in disease control with RT, the results of the current study (which we believe to have enough patients and follow-up) actually suggested that this improved control is likely to lead to improved survival in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary results (in abstract form) of the phase 2 NRG/Radiation Therapy Oncology Group (RTOG) 0539 study found that a combination of surgery/RT led to significantly improved progression-free survival in a group of patients treated for recurrent grade 1 lesions and completely resected atypical lesions. 26 This will be tested in the future with NRG Oncology protocol BN-003 and the ongoing Radiation versus Observation following surgical resection of Atypical Meningioma (ROAM)/European Organization for Research and Treatment of Cancer (EORTC)-1308 trial, for which, based on the results of the current study, we would support patient enrollment for the evaluation of disease-free-survival. 27 Although studies to date have demonstrated improvement in disease control with RT, the results of the current study (which we believe to have enough patients and follow-up) actually suggested that this improved control is likely to lead to improved survival in the future.…”
Section: Discussionmentioning
confidence: 99%
“…An important difference in the current study is that the sample size was 3 times larger, which perhaps provided enough power to allow for significance to materialize. The preliminary results (in abstract form) of the phase 2 NRG/Radiation Therapy Oncology Group (RTOG) 0539 study found that a combination of surgery/RT led to significantly improved progression‐free survival in a group of patients treated for recurrent grade 1 lesions and completely resected atypical lesions . This will be tested in the future with NRG Oncology protocol BN‐003 and the ongoing Radiation versus Observation following surgical resection of Atypical Meningioma (ROAM)/European Organization for Research and Treatment of Cancer (EORTC)‐1308 trial, for which, based on the results of the current study, we would support patient enrollment for the evaluation of disease‐free‐survival .…”
Section: Discussionmentioning
confidence: 99%
“…Target volumes were defined by the tumor bed on the postoperative MRI scan, including any nodular enhancement but excluding cerebral edema and the dural tail. A CTV margin of 1.0 cm was recommended except along natural barriers (eg, skull base) where a 0.5 cm margin was permitted, provided there was no evidence of bone invasion 9 . For reference, an RTOG-style GTV and CTV are included in Fig 4.…”
Section: Discussionmentioning
confidence: 99%
“…The dose for the eye lens is also a matter of concern in radiation therapy. The dose limit has been set to 7 Gy via the Radiation Therapy Oncology Group 0539 and 0825 studies . For tolerance doses, Emami et al reported that if the lens receives a dose of more than 10 Gy, the risk of developing cataract is 5% within/after 5 yr (TD 5/5) .…”
Section: Introductionmentioning
confidence: 99%
“…The dose limit has been set to 7 Gy via the Radiation Therapy Oncology Group 0539 and 0825 studies. 11,12 For tolerance doses, Emami et al reported that if the lens receives a dose of more than 10 Gy, the risk of developing cataract is 5% within/after 5 yr (TD 5/5). 13 This tolerance dose was defined for the conventional prescription of 1.8 or 2 Gy in a fraction, five fractions per week.…”
Section: Introductionmentioning
confidence: 99%